PENGARUH KEPEMIMPINAN, KOMUNIKASI ORGANISASI DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI SEKRETARIAT DPRD KABUPATEN TEGAL - Abdul Syukur; Edy Supriyono; Yohana Kus Suparwati (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2019)
This research uses correlation or correlational research that is by using a quantitative approach. The sample in this study were all employees and employees of the Tegal Regency DPRD Secretariat as many as 50 people. Data collection techniques using a questionnaire. The results showed that leadership (X1) and organizational culture (X3) partially had a positive and significant effect on employee performance (Y) of the Tegal Regency DPRD Secretariat. While organizational communication (X2) has a negative and significant effect on employee performance (Y) of the Tegal Regency DPRD Secretariat. With the F test results of 11,194 significance of F 0,000 and obtained t test values for leadership variables (X1) 2,858, organizational communication variables (X2) -2,325 and organizational culture (X3) 2,843. With a significance level of leadership (X1) of 0.006, organizational communication (X2) of 0, 025 and organizational culture (X3) of 0.007.